Multielectrode array characterization of human induced pluripotent stem cell derived neurons in co-culture with primary human astrocytes. - Maddie R Lemieux; Bernhard Freigassner; Jessica L Hanson; Zahra Thathey; Mark R Opp; Charles A Hoeffer; Christopher D Link (PLoS ONE)
Human induced pluripotent stem cells (hiPSCs) derived into neurons offer a powerful in vitro model to study cellular processes. One method to characterize functional network properties of these cells is using multielectrode arrays (MEAs). MEAs can measure the electrophysiological activity of cellular cultures for extended periods of time without disruption. Here we used WTC11 hiPSCs with a doxycycline-inducible neurogenin 2 (NGN2) transgene differentiated into neurons co-cultured with primary human astrocytes. We achieved a synchrony index ∼0.9 in as little as six-weeks with a mean firing rate of ∼13 Hz. Previous reports show that derived 3D brain organoids can take several months to achieve similar strong network burst synchrony. We also used this co-culture to model aspects of blood-brain barrier breakdown by using human serum. Our fully human co-culture achieved strong network burst synchrony in a fraction of the time of previous reports, making it an excellent first pass, high-throughput method for studying network properties and neurodegenerative diseases.